DIGITAL-NATIVE WORKFORCE: STRATEGI PENGEMBANGAN SDM UNTUK GENERASI Z - Ekasani, Deva; Kuswinarno, Mudji (CV SWA Anugerah, 2024)
Generation Z, who grew up in the digital era, must be able to adapt to the rapid development of technology and even bring unique characteristics to the world of work as a digital native workforce. As a generation that is technologically savvy and has different work preferences, an adaptive and innovative strategy is needed in managing human resources (HR) for Generation Z. This article